Single and combined effects of ohmic and microwave heating on crude palm oil quality and stability - Kobsak Kanjanapongkul (Agriculture and Natural Resources, 2021)
Pretreatment is a process that affects the extraction efficiency and the quality of crude palm oil (CPO). In this study, ohmic combined with microwave heating was used to pretreat oil palm fruits. The effects were evaluated of the pretreatment methods on the free fatty acids (FFA) content, peroxide value (PV), β-carotene content and energy consumption. The experiment was divided into two parts. First, either ohmic or microwave heating was used to pretreat samples. The microwave processing time was much shorter but the process required twice as much energy than the ohmic pretreatment. There were no differences between the yield and quality of the CPO obtained from the ohmic-pretreated and microwave-pretreated samples. However, when the samples were pretreated using ohmic heating followed by microwave heating, the FFA content of the CPO was lower than that pretreated using either ohmic or microwave heating (1.54% weight per weight [w/w], 1.70% w/w and 1.8% w/w, respectively) and was still lower than the critical limit even after storage for 8 wk. Furthermore, the combined process produced a slightly higher CPO yield than the single process (47% w/w and 46% w/w) while consuming 20% less energy than that required for the microwave process.